Efektivitas Mata Kuliah Mahārah Kitābah Terhadap Hasil Tulisan Mahasiswa Pendidikan Bahasa Arab - Ardea Pramesti; Nabila Nashfati; Tri Lasti; Ade Dwi Juliani; Sahkholid Nasution (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
Writing Skills is one of the four maharah studied in Arabic. Writing Skills is a way of expressing language and feelings through writing. In Writing Skills there are three elements that are trained intensively, namely, imla', khat (calligraphy) and insha'. The success of an Arabic written work can be seen from the effectiveness of the Writing Skills studied. The aim of this research is to determine the extent of the effectiveness of Writing Skills on the writing results of Arabic language education students at the North Sumatra State Islamic University Medan. This research uses qualitative methods with data collection methods using interviews and library literature. The results of this research found that the Writing Skills studied by Semester V Arabic Language Education students at the North Sumatra State Islamic University, Medan, was quite effective. Where students already understand the rules of writing Arabic properly and correctly and are able to write an essay in Arabic writing.